Metabolism of 2,3-Dehydrosilybin A and 2,3-Dehydrosilybin B: A Study with Human Hepatocytes and Recombinant UDP-Glucuronosyltransferases and Sulfotransferases - Vrba, Jiří; Papoušková, Barbora; Lněničková, Kateřina; Kosina, Pavel; Křen, Vladimír; Ulrichová, Jitka (Antioxidants, 2021)
2,3-Dehydrosilybin A and 2,3-dehydrosilybin B are a pair of enantiomers formed by the oxidation of the natural flavonolignans silybin A and silybin B, respectively. However, the antioxidant activity of 2,3-dehydrosilybin molecules is much stronger than that of their precursors. Here, we investigated the biotransformation of pure 2,3-dehydrosilybin A and 2,3-dehydrosilybin B in isolated human hepatocytes, and we also aimed to identify human UDP-glucuronosyltransferases (UGTs) and sulfotransferases (SULTs) with activity toward their respective enantiomers. After incubation with hepatocytes, both 2,3-dehydrosilybin A and 2,3-dehydrosilybin B were converted to hydroxyl derivatives, methylated hydroxyl derivatives, methyl derivatives, sulfates, and glucuronides. The products of direct conjugations predominated over those of oxidative metabolism, and glucuronides were the most abundant metabolites. Furthermore, we found that recombinant human UGTs 1A1, 1A3, 1A7, 1A8, 1A9, and 1A10 were capable of catalyzing the glucuronidation of both 2,3-dehydrosilybin A and 2,3-dehydrosilybin B. UGTs 1A1 and 1A7 showed the highest activity toward 2,3-dehydrosilybin A, and UGT1A9 showed the highest activity toward 2,3-dehydrosilybin B. The sulfation of 2,3-dehydrosilybin A and B was catalyzed by SULTs 1A1*1, 1A1*2, 1A2, 1A3, 1B1, 1C2, 1C4, and 1E1, of which SULT1A3 exhibited the highest activity toward both enantiomers. We conclude that 2,3-dehydrosilybin A and B are preferentially metabolized by conjugation reactions, and that several human UGT and SULT enzymes may play a role in these conjugations.